Challenges for Agroecology and Food Security in the Peasant Reserve Zone of Mesetas in the post-conflict scenario (Orinoquia, 2025)
This article presents the progress achieved in the Peasant Development Programs with a Territorial Approach (PDET) in the municipality of Mesetas, Meta, through the implementation of home gardens with an agroecological approach. This initiative contributes to food security, strengthens the local economy, and improves the quality of life for both producers and consumers. For this analysis, a simple random sample of members from ASODALE (Asociación Damas de Leche) was taken, and a structured survey was administered. The results reveal a significant increase in the implementation of home gardens following the peace processes, leading to diversified vegetable production for self consumption and generating surpluses for sale at farmers’ markets. Local expertise and technical assistance play a crucial role in agronomic management; however, the predominant use of non certified seeds presents a challenge. Although agroecology offers clear benefits for soil health, biodiversity, and the reduction of agrochemical use, the study identifies limitations in access to resources, technical support, and financing. The conclusion emphasizes that strengthening the connection between local knowledge and technical assistance is essential to promote sustainable agricultural development and ensure food security in the region, highlighting agroecology’s potential as a promising strategy for the development of Rural Zones Most Affected by the Armed Conflict (CRZs) in Colombia.
Keywords: Agroecology, characterisation, gardens, resilience.